Changes in perception of European integration after Brexit - Andzelika Kuznar; Jerzy Menkes (Institute of Economic Research (IER), 2017)
Research background: UK rejects the paradigm of the role and rank of the security community and the perception of European integration as a road of no return. Economic and legal study allows to assess the reasoning of Brexit and future regime of EU-UK relations. Purpose of the article: To assess changes in perception of European integration due to Brexit and to determine its geopolitical and geo-economic consequences. The reasons of such purpose: the evolving structure of the UK, persistent trends of separatism in the UK, geographical differences in attitudes of UK citizens to Brexit. Methods: The research is an interdisciplinary economic and law study. The authors use: economic and legal methods applicable to the research. Conclusions are formulated on the basis of the synthesis of the results and approximations. Findings: Brexit changes the perception and attractiveness of European integration. Weakening of Britain's ties with EU Members will have a significant impact on the strength of European identity. Brexit will weaken the European pillar of Atlantic Alliance. Brexit will be a factor of permanent disintegration of UK.
Keywords: F14; F15; F53; K33; 330; Brexit; European integration; transatlantic relations